Classification of forensic psychiatric examinations - O. P. Makarova (Bulletin of Kharkiv National University of Internal Affairs)
The article considers the classification of forensic psychiatric examinations according to various criteria. The most common is the division into types depending on the subject matter of research. According to this criterion, the following types of forensic psychiatric examinations are distinguished: